"Now Is a Time for Optimism": The Politics of Personalized Medicine in Mental Health Research. (July 2019) - Rüppel, Jonas
Since the completion of the Human Genome Project, personalized medicine has become one of the most influential visions guiding medical research. This paper focuses on the politics of personalized medicine in psychiatry as a medical specialty, which has rarely been investigated by social science scholars. I examine how this vision is being sustained and even increasingly institutionalized within the mental health arena, even though related research has repeatedly failed. Based on a document analysis and expert interviews, this article identifies discursive strategies that help to sustain this vision and its promises: "complexity talk, " "extension, " and "boundary work." These practices secure its plausibility, protect it from criticism, and maintain stakeholder support.